Pb‐Site Doping of Lead Halide Perovskites for Efficient Solar Cells. Issue 2 (4th September 2019) - Zhang, Jing; Gan, Xinlei; Sun, Hongrui; Yuan, Haobo; Yu, Luting; Hu, Ziyang; Zhu, Yuejin
Abstract : Although great success has been achieved in perovskite solar cells (PSCs), it still suffers from several drawbacks in terms of stability and higher efficiency. Doping as an effective method to modify the optical and electronic properties of the materials is extensively studied in lead halide perovskites (LHPs). Herein, Pb‐site doping in organic–inorganic hybrid perovskites (OIH‐LHPs) and inorganic CsPbX3 ‐based materials is discussed. Doping has three functions toward PSCs: participating in the crystalline process, modifying the energy states in LHPs, and contributing to the stability of PSCs. Issues about further improvements are raised, and perspectives for further investigation are presented. Abstract : Herein, Pb‐site doping in organic–inorganic hybrid perovskite (OIH‐LHP) and inorganic CsPbX3 ‐based materials is discussed, elucidating the functions of doping on lead halide perovskite (LHP) crystallization, optoelectronic property, and stability. Perspectives for further investigation are also presented.